Analysis Of Rowan Atkinson Speech Act In Johnny English Reborn Movie: English - Erick Kusuma Effendi; Lailatul Musyarofah; Yudy Prasetyo (Journal of English Development, 2024)
Johnny English reborn has been one of the interesting and particularly humorous movie. It contains dialogues or utterances that make the audience enjoy . The funny dialogue or utterances in the movie certainly contain the speech acts and it has not been investigated. Speech act is important to be studied because it can help the speaker and hearer to understand the meaning and context when they have communication. This research is to investigate the types of speech act classifications and the most dominant type of utterances produced by Rowan Atkinson in the movie. This research applied qualitative content analysis as a research design. The data in this research were taken from utterances of Rowan Atkinson. The result of research revealed that there are 40 total data of Rowan Atkinson’s utterances, Those are 10 data of Representative, 19 data of Directive, 9 data of expressive, 1 data of Commisive, and 1 data of declarative. And the most dominant subtype is informing.